Cost-Effectiveness of Drug Therapies in Management of Hypertension in a Nigerian Teaching Hospital: a Utility-Based Analysis - Giwa, Halima Bukola; Elegbede, Busayo Jumoke; Jamiu, Olakunle Muslim; Aiyelero, Oyeronke Medinat; Shittu, Abiodun Oyetunji; Njinga, Stan; Abdul, Abdulraheem; Salaudeen Giwa, Fatiu Abulfatihi; Giwa, Abdulganiyu; Elegbede, Olesegun Elijah (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Efficient resource allocation is vital for managing hypertension in Nigeria due to the high disease burden and limited healthcare resources. This study aims to assess the cost effectiveness of hypertension therapies at the University of Ilorin Teaching Hospital over one year by reviewing drug use, analyzing costs effectiveness of treatment options and examining their impact on healthcare policy and resource allocation. A sample size of 356 case notes was derived from 40,009 ambulatory hypertensive patients. The drug utilization study involved a one-year retrospective review of the 356 case notes, conducted from January to December 2023. The EuroQol 5-Dimensions 5-Level questionnaire (EQ-5D-5L) was used to determine the effectiveness of treatment options based on quality-adjusted life years (QALYs). Of the 693 prescriptions identified, 94 (13.56%) contained monotherapy, 328(47.3%) two-drug combination and 271(39.11%) three-drug combination. Amlodipine + lisinopril appeared to be more cost-effective than amlodipine + telmisartan, which in turn was more cost-effective than both amlodipine + indapamide and amlodipine + ramipril, leaving amlodipine+ lisinopril as the most cost effective out of analysed options for the Nigeria healthcare system. ICERs obtained were robust to parameter variation on probabilistic sensitivity analysis. Inclusion of Amlodipine + Lisinopril in the WHO essential medicine list, hospital formularies, and standard treatment guidelines as components of drug policy is justified and would promote rational drug use, improve treatment outcomes, and optimize resource utilization in the management of hypertension in Nigeria. Dhaka Univ. J. Pharm. Sci. 24(2): 147-156, 2025 (December)